Hubungan Terpaan Berita Korupsi Juliari Batubara dan Tingkat Kepuasan Pada PDI Perjuangan Dengan Loyalitas Konstituen PDI Perjuangan - Alya Nur Hana; Lintang Ratri Rahmiaji; Adi Nugroho (Interaksi Online, 2022)
In December 2020, there was a lot of discussion about the Covid-19 Bansos corruption case that dragged Juliari Batubara's name as the minister of social affairs of the Republic of Indonesia who is also part of the PDI Perjuangan. On the basis of this act, Juliari was sentenced to 12 years in prison. Political parties are institutions that get a low level of satisfaction from the community, political parties are considered unclean and oriented to self-interest or class. Although many PDI Perjuangan cadres are corrupt, and the public is dissatisfied with the existence of political parties, the position of PDI Perjuangan is still strong and dominated, this is seen in the results of the 2020 election where PDI Perjuangan became the most widely chosen party. The purpose of this study is to find out the correlation between the exposure of news about the corruption of Juliari Batubara with the loyalty of PDI-Perjuangan constituents and also the correlation between the level of satisfaction in the political party and the loyalty of PDI-Perjuangan constituents. This research is an explanatory quantitative research with a positivistic paradigm guided by Social Cognitive Theory and the integration between Satisfaction Theory – Loyalty and Hope Confirmation Theory. The correlation test uses Kendall Tau with the help of SPSS version 26 with nonprobability sampling techniques precisely using purposive sampling. This study was followed by 60 PDI Perjuangan voters in Central Java who had been exposed to news of Juliari Batubara corruption at least twice. The results showed that there was no correlation between the exposure of juliari Batubara corruption news (X1) and the loyalty of PDI Perjuangan (Y) constituents because the significance figure was 0.796. On the other hand, there is a correlation between satisfaction in PDI Perjuangan (X2) and the loyalty of PDI Perjuangan constituents (Y) with a significance of 0,000, the strength of the correlation is very strong, and the direction of the correlation between the variables of satisfaction and loyalty is positive or directly proportional.